The Role of Counseling Guidance in Tackling Adolescent Mental Health Problems - Salim Azim, Agus (Journal of Educational Studies, 2023)
This article discusses the role of guidance counseling in tackling adolescent mental health problems. Adolescent mental health is increasingly becoming a serious concern because of its significant impact on their lives socially, emotionally, and academically. Guidance counseling is known as a holistic approach to help adolescents overcome their mental health issues. The method used in this article is a literature review involving studies related to the role of guidance counseling in tackling adolescent mental health problems. The results of this analysis suggest that guidance counseling has an important role to play as a means to diagnose, prevent, treat, and support adolescents in dealing with their mental health problems. Through appropriate interventions, counseling guidance can help adolescents have good mental health, improve their quality of life, and reach their optimal potential.